The Contraceptive Effect of the Extract Methanol of The Leaves Hydrocotyle Javanica Thumb on Female Mice - Rinidar R; M. Isa (Jurnal Kedokteran Hewan, 2007)
The aim of this study is to investigate the contraceptive effect of the extract methanol of the leavesHydrocotyle javanica Thumb and its effect threat of implantation, the quantity and condition of fetuses,histology appearance of the ovary and uterus and rate of pregnancy. The female mice were given orallyeither methanol extract of leaves, for 10 days in various doses: 20, 40, 60, and 80 gram/kg BW. On day20, the mice were mated and when pregnancy occurred, treatment was stopped. On day 17 of pregnancy,the mice were sacrificed: uterus and ovaries were examined histologically. In conclusion, methanol extractof Hydrocotyle javanica Thumb shows contraceptive activity (P 0.05).Keywords: extract methanol, Hydrocotyle javanica Thumb, contraceptive